Comparison of repetitive transcranial magnetic stimulation and intermittent theta burst stimulation efficacy in treating post-stroke dysphagia: a prospective, single-blind, randomized controlled study - Li, Fang; Cheng, Jinling; Zhu, Yanying; Peng, Yang; Liu, Zicai (Frontiers in Neurology, 2025)
ObjectiveTo compare the efficacy of repetitive transcranial magnetic stimulation (rTMS) and intermittent theta burst stimulation (iTBS) applied to the motor cortex representation of the mylohyoid muscle in treating post-stroke dysphagia.MethodsNinety-two patients with post-stroke dysphagia (July 2022–May 2023) were randomized into three groups: rTMS (n = 31), iTBS (n = 30), and control (n = 31). The rTMS and iTBS groups received respective stimulations plus routine rehabilitation; the control group received routine rehabilitation alone. Swallowing function was assessed pre- and post-intervention using the Penetration-Aspiration Scale (PAS) and Dysphagia Disability Index (DD).ResultsAfter 2 weeks, all groups showed significant swallowing improvement (p < 0.001). Both rTMS and iTBS groups demonstrated greater improvement in PAS and DD scores versus controls (p < 0.001). No significant difference emerged between rTMS and iTBS efficacy (p > 0.05).ConclusionrTMS and iTBS equivalently improve post-stroke dysphagia. iTBS achieves comparable outcomes with shorter treatment duration, supporting its clinical adoption.Clinical trial registrationIdentifier ChiCTR2200058246, https://www.chictr.org.cn/.